IMPLEMENTATION OF RESTORATIVE JUSTICE IN THE SETTLEMENT OF VIOLENT CRIMINAL ACTIONS IN THE HOUSE OF TNI SERVANTS IN THE MILITARY JUSTICE SYSTEM - Nentin Feriyanti; Ramlani Lina Sinaulan; Moch Haris (Journal of Industrial Engineering & Management Research, 2023)
The rise of domestic violence cases in Indonesia does not only occur in civil society but also occurs in the TNI environment, in fact there have been several cases of TNI soldiers committing domestic violence. In the process of law enforcement of domestic violence, TNI soldiers are almost entirely sentenced to imprisonment. Whereas there is an alternative resolution through restorative justice which in the military justice system there are no rules regarding the application of restorative justice as a guideline for implementation in contrast to the general court which has been regulated in the Supreme Court regulations. Therefore, this research aims to discuss the application of Restorative Justice to support efforts to restore the situation to its original state as the purpose of Law Number 23 of 2004 concerning the Elimination of Domestic Violence. The method used in this research is normative juridical supported by a case approach taken from decisions of the Jakarta and Bandung Military Courts as well as statutory and literature studies followed by analyzing by means of systematic interpretation. The results of this study indicate that the principle of Restorative Justice has been applied by the Panel of Judges in several cases of domestic violence of TNI Soldiers through considerations of decisions, although there are no provisions governing the application of Restorative Justice in the military justice system as guidelines, but in practice it has been applied. Therefore, it is necessary to issue SEMA and internal TNI provisions so that they can serve as guidelines for the Military Court Judges in applying Restorative Justice in the Military Justice System.